Environmental Graphic Design as An Information Media for The Mecca Area Park - Zenmira, Kharisma Nanda; Kholifah, Yuli (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
The Mecca Park in Pasuruan City is a religious tourism destination with strategic potential but faces the problem of a lack of adequate visual information systems. This study aims to design a comprehensive and effective Environmental Graphic Design (EGD) as an information medium to improve the quality of visual services and tourist experiences. The research method uses a Research and Development (R&D) approach with the Sugiyono model simplified into 7 stages. The research subjects consisted of 10 respondents for the small-scale trial and 82 respondents for the large-scale trial. The design concept developed is